Incidence of milling energy on dry-milling attributes of rice starch modified by planetary ball milling - González, Luciana Carla (2018)
Rice starch was modified in a planetary mill. The effects of milling energy (E) on physicochemical and functional properties were investigated. Particle size, crystallinity degree and gelatinization enthalpy were reduced with the increase of milling energy. The effect of E on particle size reduction could be predicted by generalized Holmes' model. Heat dissipation was evidenced during milling through the non-linear relationship between size reduction ratio and milling energy. Hydration and pasting properties were significantly affected. Water soluble index (WSI) and swelling power (SP) increased with increasing both energy and temperature of hydration test. For the greatest energy and temperature level (85 °C), WSI value varied between 1.5 and 29.7% and SP value between 7.4 and 16.4  g/g, relative to native starch. The crystallinity showed negative relationships with WSI and a SP. Regards to pasting properties, peak viscosity (PV) decreased from 4384 mPa s to 544 mPa s as E varied between 0 kJ/g and 4.08 kJ/g. Peak, setback and final viscosities parameters showed a linear relationship with the particle size. There were found strong correlations between physicochemical and functional properties of modified starches, which evidenced the dependence of the modification on milling severity. Planetary ball milling is presented as an eco-friendly alternative to modify native rice starch properties.